Engineering the interfaces in MgO-modified Ni/Al2O3 for CO2 methanation - Xie, Yufei; Lips, Servaas; D’ooghe, Lennert; Sabbe, Maarten; Detavernier, Christophe; Poelman, Hilde; Galvita, Vladimir (Applied catalysis. A, General, 2024)
The interaction between metallic active phases and oxides is of great significance for catalytic properties, but still remains elusive. Here, two reverse interfaces are constructed (Ni/MgO and MgO/Ni on Al2O3) for a typical CO2 methanation catalyst, Ni/Al2O3, by depositing Ni and MgO in opposite sequences on Al2O3. Enhanced performance was found on both interface structures, however, distinct turnover frequencies indicate different mechanisms. With MgO present in between Ni and Al2O3, the formation of an inactive NiAl2O4 spinel phase is mitigated, making more NiO available for reduction. When MgO is added on top of Ni, the new MgO/Ni interface exhibits high reactivity in CO2 methanation. CO2 temperature programmed desorption, in situ quick X-ray adsorption spectroscopy (QXAS) and modulation excitation XAS (MEXAS) demonstrate that a Ni-NiO redox mechanism occurs with enhanced CO2 activation at the MgO/Ni interface. The subsequent hydrogenation of adsorbed carbon monoxide and carbonate species requires nearby Ni to provide H spillover and occurs preferably at the interface sites, where adsorbed species are more easily activated. Hence, interfaces between the same compounds, but with reverse structures, result in different phenomena, illustrating the role an interface structure can play in catalytic systems. [Display omitted] •Catalysts with spatially reversed interface structure, Ni/MgO-Al2O3 and MgO-Ni/Al2O3, exhibit distinct catalytic properties.•MgO in between Ni and Al2O3 mitigates their interaction, i.e. Ni/MgO-Al2O3.•Depositing MgO on Ni generates a new MgO/Ni interface, i.e. MgO-Ni/Al2O3.•CO2 gets activated at the interface sites, yielding CO and O that oxidizes Ni.•CO2 methanation follows from hydrogenation of carbonate and adsorbed CO.